A tale of two studies: Detection and attribution of the impacts of invasive plants in observational surveys. Issue 4 (23rd January 2018) - Mueller, Kevin E.; Lodge, Alexandra G.; Roth, Alexander M.; Whitfeld, Timothy J. S.; Hobbie, Sarah E.; Reich, Peter B.
Abstract: Short‐term experiments cannot characterize how long‐lived, invasive shrubs influence ecological properties that can be slow to change, including native diversity and soil fertility. Observational studies are thus necessary, but often suffer from methodological issues. To highlight ways of improving the design and interpretation of observational studies that assess the impacts of invasive plants, we compare two studies of nutrient cycling and earthworms along two separate gradients of invasive shrub abundance. By considering the divergent sampling strategies and statistical analyses of these two studies, and interpreting their contradictory results in the context of other studies, we also aim to better describe the impacts of the focal invader, Rhamnus cathartica . In a new study of a single site in Minnesota, we observed positive correlations between buckthorn abundance and soil pH, soil nutrient pools, nutrient fluxes through leaf litterfall, earthworm abundance and root biomass. Multiple regression models showed these relationships persisted after accounting for variability in soil texture and tree species composition. For a separate, more expansive study in Illinois, other authors reported little to no correlation between buckthorn abundance and 10 soil properties, including earthworm abundance, pH and nutrient concentrations. However, like many other studies, their regression models only assessed predictors related to invader abundance. R 2 ‐values for models of ecosystem properties ranged from 0 to .79 (adjusted‐ R 2 ) for our study in Minnesota and from <.05 to .16 (unadjusted) for the prior study in Illinois. Differences in sampling error and use of predictor variables between the two studies likely explain the contrasting results. Synthesis and applications . To reduce the uncertainty of conclusions from observational studies of invasive plants, future studies must ensure that heterogeneity of soils and vegetation is adequately accounted for in the sampling strategy and statistical analyses (e.g. analysis of covariance, multiple regression). Particular attention should be given to ecosystem properties with variability that likely pre‐dates the invader (e.g. geophysical features and tree community composition). In our study, effects of buckthorn on ecosystem properties were not only robust to the inclusion of potentially confounding predictors, but also consistent with expectations based on ecological stoichiometry and mass balance of element flow. Abstract : To reduce the uncertainty of conclusions from observational studies of invasive plants, future studies must ensure that heterogeneity of soils and vegetation is adequately accounted for in the sampling strategy and statistical analyses (e.g. analysis of covariance, multiple regression). Particular attention should be given to ecosystem properties with variability that likely pre‐dates the invader (e.g. geophysical features and tree community composition). In our study, effects of buckthorn on ecosystem properties were not only robust to the inclusion of potentially confounding predictors, but also consistent with expectations based on ecological stoichiometry and mass balance of element flow.